The socio-political system and development - Klemens Sand (Intereconomics, 1995)
The traditional focus of development cooperation on economic growth and the transfer of technology having proved insufficient, it would seem that an international consensus on the objectives and essence of development is now emerging which places strong emphasis on participation of the people and on human rights. The way in which this fundamental consensus is to be translated into actual policy, however, continues to be unclear and even contentious.
Keywords: 330; Development Strategy